Gerakan Sewu-Sewu Ae: Peran Nyata Pemuda Mengarungi Pandemi - Jannah, Salsabilah Shofiyatul; Alamsyah, Anrico; Yunarko, Dika Ifanda (Jurnal ENTITAS SOSIOLOGI, 2022)
This article aims at explaining Sewu-Sewu Ae movement which is held by the youth in Madiun city during the Pandemic of COVID-19. It is a movement initiated from some concerns from the youth toward what happened to society especially in the time of PPKM period. This is a participatory approach as one of the authors is a pioneer of the movement. The research objective is to analyze several fundamental values, innovations, operational systems, and evaluations in the Sewu-Sewu Ae movement. Data were collected using observation, documentation, and interviews. The results of the study found that one of the biggest challenges of the society was economic difficulty. Although government has provided solutions, the implementation was complicated by the system. Reflecting from this reality, the youth took a step to take roles on this matter. During the pandemic, philanthropy-based social movements are increasingly prevalent in several cities, for example, the "Solidaritas Pangan Jogja” which started on March 2020. In essence, every social movement has its own characteristics. Likewise Sewu-Sewu Ae which was initiated by the youth of Madiun City. This fundraising movement was channeled in a program "Melariskan UMKM", "Distribusi Paket Sembako", and the latest innovation entitled "Pasar Sewu". This movement has proven to be consistent and sustainable, so that it continues to gain support from public. Sewu-Sewu Ae is able to become a medium for surrounding community to actualize social sensitivity. Keywords: Madiun, social movement, Sewu-Sewu Ae, youth Tulisan ini bertujuan menjelaskan tentang gerakan sosial Sewu-Sewu Ae pada masyarakat Madiun di era pandemi. Kegiatan ini merupakan gerakan sosial berbasis solidaritas sosial, yang berlandaskan pada keprihatinan pemuda terhadap realitas masyarakat di masa PPKM. Penelitian ini menggunakan paradigma kualitatif dengan pendekatan partisipatoris. Pengumpulan data dilakukan dengan menggunakan metode observasi, dokumentasi, dan juga wawancara. Hasil penelitian menemukan bahwa salah satu problematika terkini adalah kesulitan ekonomi. Kendatipun pemerintah telah memberikan solusi berupa pengadaan bantuan sosial, namun implementasinya menghadapi berbagai kendala sistem. Oleh karena itu, perlu peran nyata pemuda untuk memecahkan persoalan tersebut. Pada masa pandemi, gerakan sosial berbasis filantropi kian marak di beberapa kota. Contohnya gerakan “Solidaritas Pangan Jogja” yang dimulai sejak Maret 2020. Pada hakikatnya, setiap gerakan sosial memiliki ciri khas masing-masing. Begitu pula Sewu-Sewu Ae yang diprakarsai oleh pemuda Kota Madiun. Gerakan penggalangan dana ini disalurkan dalam bentuk program “Melariskan UMKM”, "Distribusi Paket Sembako", serta inovasi terbaru bertajuk “Pasar Sewu”. Gerakan ini terbukti konsisten dan berkelanjutan, sehingga terus memperoleh dukungan khalayak umum. Sewu-Sewu Ae mampu menjadi medium bagi masyarakat sekitar untuk mengaktualisasikan kepekaan sosial. Kata kunci: gerakan sosial, pemuda, Sewu-Sewu Ae